The vitamin D status in a Chinese osteogenesis imperfecta population and its correlation with bone metabolic markers and bone density - Jiang, Yunyi; Mei, Yazhao; Tian, Yuan; Shen, Li; Xu, Shuqin; Zhang, Hao; Zhang, Zhenlin (Frontiers in Nutrition, 2024)
Objective: Studies on the baseline vitamin D levels in osteogenesis imperfecta (OI) patients before medication are scarce. This study assessed the vitamin D status of a population with OI at both the overall level and within different age groups. It correlated baseline 25-hydroxyvitamin D (25(OH)D) levels with other bone-related factors, biochemical markers, and bone density.We collected 25-hydroxyvitamin D (25(OH)D) levels from 95 OI patients in East China (59 under 18 years old and 36 over 18 years old). Patients who were postmenopausal, males over 50 years old). Measurements included body indicators, biochemical markers, and bone mineral density (BMD) assessed by Dual-energy X-ray absorptiometry (DXA). Data analysis was performed using SPSS 26.0.In the overall population, among those under 18 years old, and among those over 18 years old, 87.4%, 83.1%, and 94.4% respectively were vitamin D deficient (<30 ng/mL), while 47.4%, 40.7%, and 58.3% had vitamin D deficiency (<20 ng/mL), respectively. In the overall population and among those under 18 years old, serum 25(OH)D levels were negatively correlated with age and parathyroid hormone (PTH) levels, and 25(OH)D levels (<10 ng/mL, 10-20 ng/mL, 20-30 ng/mL, >30 ng/mL) showed a negative correlation with BMI. In OI patients under 18 years old, serum 25(OH)D was negatively correlated with serum β-CTX levels. In adult male OI population, 25(OH)D levels were negatively correlated with OI severity (Type I, IV, III). No statistically significant correlation was found between 25(OH)D levels and bone density Z scores.This study on OI in East China reveals significant vitamin D insufficiency and deficiency in baseline levels among pediatric, adolescent and adult OI patients. It assesses the correlation of 25(OH)D levels with various influencing factors, providing crucial insights into understanding the impact of OI on vitamin D status across different age groups and aiding in better clinical management of OI patients.